2016
DOI: 10.1038/srep20532
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Atp-Dependent Chromatin Remodeling Factors: Smarcal1 and Brg1 Mutually Co-Regulate Each Other

Abstract: The ATP-dependent chromatin remodeling factors regulate gene expression. However, it is not known whether these factors regulate each other. Given the ability of these factors to regulate the accessibility of DNA to transcription factors, we postulate that one ATP-dependent chromatin remodeling factor should be able to regulate the transcription of another ATP-dependent chromatin remodeling factor. In this paper, we show that BRG1 and SMARCAL1, both members of the ATP-dependent chromatin remodeling protein fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 42 publications
(65 reference statements)
1
46
0
Order By: Relevance
“…One report suggests SMARCAL1 localization is cell cycle regulated where it is predominately nuclear during S phase through mitosis but is exported to the cytoplasm during the first growth phase of the cell cycle (G 1 ) (Haokip et al , 2016). This study also indicated SMARCAL1 transcript expression is DNA damage-dependent (Haokip et al , 2016). However, these observations require further validation in additional systems.…”
Section: Smarcal1mentioning
confidence: 99%
See 2 more Smart Citations
“…One report suggests SMARCAL1 localization is cell cycle regulated where it is predominately nuclear during S phase through mitosis but is exported to the cytoplasm during the first growth phase of the cell cycle (G 1 ) (Haokip et al , 2016). This study also indicated SMARCAL1 transcript expression is DNA damage-dependent (Haokip et al , 2016). However, these observations require further validation in additional systems.…”
Section: Smarcal1mentioning
confidence: 99%
“…SMARCAL1 also has been reported to have a regulatory role in the transcription of a subset of genes (Baradaran-Heravi et al , 2012b, Sharma et al , 2015, Haokip et al , 2016, Patne et al , 2017). Specifically, SMARCAL1 was reported to directly modify the chromatin near promoter sequences to regulate gene expression especially in cells experiencing replication stress (Sharma et al , 2015, Haokip et al , 2016, Patne et al , 2017).…”
Section: Smarcal1mentioning
confidence: 99%
See 1 more Smart Citation
“…2B; Supplementary Excel File 3 and 4). Previously, we had shown that SMARCAL1 was present on BRG1 promoter and BRG1 was present on SMARCAL1 promoter 24 . The ChIP-seq data validated our experimental results ( Fig.…”
Section: The Transcriptomic Profile Of Hela Cells Is Altered On Treatmentioning
confidence: 95%
“…1G). The ATPase activity of these proteins is needed for co-regulating transcription [24][25][26][27] . Also, we had previously shown that cell line resistant to ADAADiN showed decreased ATPase activity of SMARCAL1 and BRG1 that manifested in alterations in the transcriptomic profile of the cells 6 .…”
Section: The Transcriptomic Profile Of Hela Cells Is Altered On Treatmentioning
confidence: 99%